Development of sulfonated poly(vinyl alcohol)/polpyrrole based ionic polymer metal composite (IPMC) actuator and its characterization. (30th July 2015) - Inamuddin,; Khan, Ajahar; Jain, R K; Naushad, Mu
Abstract: In the present study, a novel sulfonated poly(vinyl alcohol)/polypyrrole polymer membrane sandwiched between platinum (SPVA-Py-Pt) is fabricated for a bending actuator which can be used in microrobotic applications. To examine the suitability of SPVA-Py-Pt based ionic polymer metal composite (IPMC) for microrobotic applications, ion exchange capacity (IEC), water uptake, proton conductivity, water loss, cyclic voltammetry (CV), linear sweep voltammetry (LSV), Fourier transform infrared spectroscopy (FTIR), thermal stability, and tip displacement studies are performed. The water holding capacity of the IPMC membrane is found to be 82.23% at room temperature for 8 h of immersion time. The IEC and proton conductivity of the IPMC membrane is found to be 1.2 meq g −1 and 1.6 × 10 −3 S cm −1, respectively. Maximum water loss from IPMC is achieved as 31% at 5 V for a time period of 16 min. Based on electromechanical characterization, the maximum tip displacement of SPVA-Py-Pt IPMC (size 30 mm length, 10 mm width, 0.08 mm thickness) is 18.5 mm at 5.25 V. The major advantages of this new type of IPMC are good film-forming capability, short processing time, low cost of fabrication, good flexibility, high thermo-mechanical stabilities, good ion exchange and water holding capacities and proton conductivity as compared to other types of IPMC actuators. The comparison with other type of IPMC actuators is also summarized. A multi SPVA-Py-Pt IPMC based micro-gripping system is developed that shows the potential of microrobotic applications.